ANALISIS KUALITAS AIR PADA SISTEM PENGAIRAN AKUAPONIK [Analysis of Water Quality in Aquaponic Irrigation System] - Nur Fitria Farida; Sirajuddin Haji Abdullah; Asih Priyati (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2017)
Land conservation has impact on limitation of land and water for agriculture purposes. Availability of water and its quality has effect on plant growth and productivity. Water processing can be done through several ways among other is through aquaponics system. Aquaponics is one of alternative that can be applied to land that have limited water. Therefore, this research aimed to analysis the water quality on two aquaponics irrigations system and to measure the growth and productivity of red spinach. In this study two Aquaponics irrigation systems with three stage were used, which is ebb and flow (A11, A12, A13) and floating rafts (A21, A22, A23). Parameters used in this study are dissolved oxygen, electrical conductivity, total dissolved solid, salinity, ammonia, pH, growth and productivity of red spinach. Result of this study showed that each treatment in different stage had different average value of each parameter. Values of measured dissolved oxygen at ebb and flow treatment respectively A11 = 2.60 mg/l, A12 = 2.62 mg/l, A13 = 2.57 mg/l and at floating rafts respectively A21 = 2.50 mg/l, A22 = 2.44 mg/l, A23 = 2.36 mg/l. Values of electrical conductivity at ebb and flow treatment respectively A11 = 1.55 mS/cm, A12 = 1.53 mS/cm, A13 = 1.51 mS/cm and at floating raft A21 = 1.56 mS/cm, A22 = 1.56 mS/cm, A23 = 1.56 mS/cm. Average value of total dissolved solid in the ebb and flow respectively A11 = 987.8 ppm, A12 = 976.5 ppm, A13 = 965.8 ppm and at floating rafts respectively A21 = 996.5 ppm, A22 = 998.0 ppm, A23 = 999.3 ppm. Average value of salinity obtained at ebb and flow was A11 = 0.98 ppt, A12 = 0.93 ppt, A13 = 0.90 ppt and at floating rafts was A21 = 0.95 ppt, A22 = 0.98 ppt, A23 = 0.98 ppt. Ammonia value at ebb and flow was A11 = 0.025 mg/l, A12 = 0.025 mg/l, A13 = 0.024 mg/l and at floating rafts was A21 = 0.067 mg/l, A22 = 0,039 mg/l, A23 = 0,039 mg/l. Average pH value on first, second, and third stage at ebb and flow was 7.2 and at floating rafts was 7.3. Water quality affect the growth of plant height, leaves width, leaves number, weight of the plant, and plant productivity of red spinach. Keywords: aquaponics, water quality, plant growth, plant productivity ABSTRAK Konversi lahan berdampak pada keterbatasan luas lahan dan jumlah air dari berbagai aspek terutama pada pertanian. Kebutuhan air serta kualitas air pada bidang pertanian sangat berpengaruh terhadap pertumbuhan dan produktivitas tanaman. Pengairan untuk tanaman dapat dilakukan dengan berbagai macam cara, misalnya akuaponik. Akuaponik merupakan salah satu alternatif yang dapat diterapkan pada lahan yang sempit dan memiliki keterbatasan air. Oleh karena itu, penelitian ini bertujuan untuk mengkaji kualitas air pada dua perlakuan sistem pengairan akuaponik dan mengukur pertumbuhan dan produktivitas tanaman bayam merah. Pada penelitian ini digunakan dua sistem pengairan akuaponik dengan tiga tingkatan, yaitu perlakuan pasang surut (A11, A12, A13) dan rakit apung (A21, A22, A23). Parameter yang di teliti, yaitu: oksigen terlarut, daya hantar listrik, total dissolved solid, salinitas, amonia, pH, pertumbuhan dan produktivitas tanaman. Data yang diperoleh pada kedua perlakuan memiliki nilai rata-rata yang berbeda di setiap tingkatan. Nilai oksigen terlarut yang terukur pada perlakuan pasang surut sebesar A11 = 2,60 mg/l, A12 = 2,62 mg/l, A13 = 2,57 mg/l dan rakit apung A21 = 2,50 mg/l, A22 = 2,44 mg/l, A23 = 2,36 mg/l. Nilai daya hantar listrik pada perlakuan pasang surut sebesar A11 = 1,55 mS/cm, A12 = 1,53 mS/cm, A13 = 1,51 mS/cm dan rakit apung sebesar A21 = 1,56 mS/cm, A22 = 1,56 mS/cm, A23 = 1,56 mS/cm. Nilai total dissolved solid pada pasang surut sebesar A11 = 987,8 ppm, A12 = 976,5 ppm, A13 = 965,8 ppm dan rakit apung sebesar A21 = 996,5 ppm, A22 = 998,0 ppm, A23 = 999,3 ppm. Nilai rata-rata salinitas pada perlakuan pasang surut didapat sebesar A11 = 0,98 ppt, A12 = 0,93 ppt, A13 = 0,90 ppt dan rakit apung sebesar A21 = 0,95 ppt, A22 = 0,98 ppt, A23 = 0,98 ppt. Nilai amonia pada pasang surut sebesar A11 = 0,025 mg/l, A12 =0,025 mg/l, A13 = 0,024 mg/l dan rakit apung A21 = 0,067 mg/l, A22 = 0,039 mg/l, A23 = 0,039 mg/l. Nilai rata-rata pH baik tingkat satu, dua, dan tiga pada perlakuan pasang surut sebesar 7,2 dan rakit apung sebesar 7,3. Kualitas air yang didapatkan berpengaruh terhadap peningkatan pertumbuhan baik dari tinggi tanaman, lebar daun, jumlah daun, berat tanaman, dan produktivitas tanaman. Kata kunci: akuaponik, kualitas air, pertumbuhan tanaman, produktivitas tanaman